2010
DOI: 10.1007/s00701-010-0709-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain and brachial plexus lesions: evaluation of initial outcomes after reconstructive microsurgery and validation of a new pain severity scale

Abstract: We have designed and tested a simple and reliable method by which to quantify neuropathic pain after traumatic brachial plexus injuries. Initial surgical treatment of the paralysis--including nerve, trunk and root reconstruction, and neurolysis--comprises an effective means by which to initially treat neuropathic pain. Ablative or neuromodulative procedures, like dorsal root entry zone, should be reserved for refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Although some literature reported that the BPA model produces long lasting mechanical and cold allodynia in all rats [10]. However, in accordance with previous studies, not all the BPA patients developed neuropathic pain [2,12,14]. The study reported that the incidence of neuropathic pain after complete BPA was 83.3% [14].…”
Section: Introductionsupporting
confidence: 76%
“…Although some literature reported that the BPA model produces long lasting mechanical and cold allodynia in all rats [10]. However, in accordance with previous studies, not all the BPA patients developed neuropathic pain [2,12,14]. The study reported that the incidence of neuropathic pain after complete BPA was 83.3% [14].…”
Section: Introductionsupporting
confidence: 76%
“…The paroxysmal pain is felt in the arm [26]. Allodynia, hypersensitivity and electric-like discharges are present at the border between the normal and affected dermatomes [17,[26][27][28][29], particularly between T 1 and T 2 at the posterior aspect of the elbow [26].The pain severity correlates with the magnitude of the brachial plexus injury [2,3] and to the number of avulsed nerve roots [2-4, 21, 26, 30-33], particularly when the lower roots are affected [24,34,35]. Nevertheless, Bertelli et al [21] found that in isolated C 8 and T 1 nerve root avulsions, there was no pain at all.The pain does not appear immediately after the injury but a few days later [24] and no longer than 3 months after it [5, 6, 24, 26,35,36].The neuropathic pain can be associated with phantom [37] or stump pain [38] in case of upper limb amputation, or to complex regional pain syndrome (CRPS) [6], inducing a complex pain condition rather difficult to control [19,30,31].Self-mutilation has been described in 5-29% of obstetric brachial plexus injury cases [39,40].The quality of life is seriously impaired with sleep disorders, family troubles, unemployment, chronic depression and social withdrawal [2, 5, 6, 17, 21,[41][42][43][44].…”
mentioning
confidence: 99%
“…The pain severity correlates with the magnitude of the brachial plexus injury [2,3] and to the number of avulsed nerve roots [2-4, 21, 26, 30-33], particularly when the lower roots are affected [24,34,35]. Nevertheless, Bertelli et al [21] found that in isolated C 8 and T 1 nerve root avulsions, there was no pain at all.…”
mentioning
confidence: 99%
“…Patients are initially treated medically with a combination of anticonvulsants, antidepressants, nonsteroidal anti-inflammatory drugs, or opioids. Surgical procedures for repair of brachial plexus lesions, like repair with autologous grafts, extraplexual or intraplexual nerve transfers, are reported to help in relieving the pain in some cases [4]. If pain persists despite medical management or surgical repair, other invasive treatment modalities like DREZ lesioning and cervical SCS are indicated.…”
Section: Cervical Spinal Cord Stimulation For the Management Of Pain mentioning
confidence: 99%
“…In addition, a few patients develop local alopecia or other trophic changes [3]. NH was described in 2002 [1], and has already been reported in 238 cases according to a recent review [4]. Although NH emerged as a primary disorder, we have to pay attention to possible symptomatic or secondary cases.…”
Section: Nummular Headache In a Patient With Craniosynostosis: One Momentioning
confidence: 99%